Physicochemical Characterization and Cytocompatibility Study of Lyophilized Cow Urine Powder - Pallawi; Vishwakarma, Neeraj K.; Paulraj, Sushmitha; Mahto, Sanjeev Kumar; Singh, Kameshwarnath (Informatics Publishing Limited and Society for Biocontrol Advancement, 2023)
Cow urine is known for possessing therapeutic potency which is found to vary depending upon its physical forms such as fresh sterile urine, distillate, lyophilized powder, etc. In the current work, we demonstrate the physicochemical characteristics and cytocompatibility of lyophilized powder of cow urine obtained from Sahiwal and the pure Indian breed. We have used several analytical techniques, including Thermogravimetric Analysis (TGA), Fourier Transform Infrared (FTIR) Spectroscopy, Differential Scanning Calorimetry (DSC), Nuclear Magnetic Resonance (NMR) spectroscopy and Scanning Electron Microscopy – Energy Dispersive X-ray Spectroscopy (SEM-EDX) to examine the physical and chemical nature of cow urine powder obtained through lyophilization. SEM-EDX analysis showed clusters like morphology and revealed 25-30% of metal ions present in both samples. TGA analysis showed three steps of degradation sequentially most likely due to initial desorption of adsorbed water, urea degradation, and loss of glycoside moiety present in flavonoid. DSC data revealed the presence of both irregular (amorphous) and ordered molecular structures (crystalline) in the lyophilized powder of cow urine.1H NMR spectra of all the prepared cow urine samples exhibited a similar trend and did not vary significantly and; confirming the presence of the same flavonoid/compounds in each sample. FTIR spectra of all the prepared cow urine samples exhibited a similar trend and did not vary significantly as observed through1H NMR spectra. In addition, a cytocompatibility study and MTT assay using NIH-3T3 fibroblast cells revealed that lyophilized cow urine powders possessed no deleterious effects on healthy fibroblast cells. Thus, the outcomes provide a benchmark for further understanding of the lyophilized form of cow urine that could be potentially useful for analyzing its therapeutic value.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Analytical Techniques; Fibroblast Cells; Indian Breed; Sahiwal; flavonoid; glycoside; metal ion; urea; water